SMART CONTENT SEARCH FROM AUDIO/VIDEO CAPTURES WHILE WATCHING TV CONTENT ITSELF - Yang, Yunfeng; Barbieri, John D (2025)
According to principles of the disclosure, additional information about a subject of interest appearing in an audio/video program is conveyed to a user. The user, interacting with various features of a control device, provides one or more commands to a computing device acting as a source for audio/video content. The one or more command is interpreted by the computing device to identify the user's subject of interest. Once the user's subject of interest is determined, an appropriate database is searched for additional information about the subject of interest. Search results are processed and conveyed to the user through a display, speaker, or other appropriate means.